Efeito protetor da amitriptilina in vitro na disfunção endotelial e nas alterações oxidativas e pró-inflamatórias induzidas pela LDL oxidada - Thais Lemos Ferreira (2022)
Atherosclerosis is an inflammatory disease that occurs in the subendothelial layer of the arteries due to oxLDL accumulation. Even though there are many avaiable treatments for atherosclerosis, cardiovascular diseases are still the leading causes of death worldwide thus more therapeutic options are needed. Drug repositioning (also known as drug repurposing) is an interesting approach because it enables new clinical indications for drugs with well-established pharmacological properties. Amitriptyline (AM) is an antidepressant drug that has been used to treat pain and inflammatory disorders because of its anti-inflammatory action, thus it could also be used to regulate the inflammatory component of atherosclerosis. The purpose of this study was to investigate AM effects in the dysfunction and in vitro inflammation caused by oxLDL (50 μg/mL) in murine aortas and macrophages (RAW264.7), and in human endothelial cells (EA.hy926). Phenilephrin concentration-response curves were recorded on a wire myograph. Cell alterations were evaluated by fluorescence microscopy, flow cytometry and ELISA assays. Incubation with AM (0,1 μM) reverted the oxLDL-induced decreased vasoconstriction in murine aortas and the oxLDL-induced increase in NO concentration and iNOS expression in endothelial cells. AM did not increase eNOS and nNOS expression nor the ACh-stimulated nitric oxide (NO) concentration that were diminished by oxLDL incubation. AM did not reduce NADPHox augmentation in endothelial cells, but superoxide levels were reduced. Also, AM was able to lower the calcium transient increased by lysophosphatidylcholine (LPC) both at basal state and after ACh stimulation in endothelial cells. In macrophages, incubation with AM attenuated the oxLDL uptake by lowering SRA receptor expression, resulting in both reduced cytokine (CCL2, IL-6, IL-1β and TNF) levels and iNOS expression. The results show that AM was able to prevent the proinflammatory and oxidative changes induced by LDLox, reducing pro-inflammatory cytokines and iNOS expression, which contributes to a less oxidative state. Taken together, these results show that low concentrations of AM have the potential to ameliorate pro-inflammatory events and oxidative stress caused by oxLDL, although more studies are needed to fully understand the mechanism of action of this drug.